2013
DOI: 10.1016/j.biortech.2013.08.085
|View full text |Cite
|
Sign up to set email alerts
|

Landfill leachate treatment as measured by nitrogen transformations in stabilization ponds

Abstract: The treatment performance and nitrogen mass balance of a pilot-scale landfill leachate treatment system was evaluated. The system was comprised of a series of three ponds and a rock filter and was fed a continuous flow (200 L d(-1)) during 111 weeks. Three different operational conditions were investigated: conventional operation (stage I), aeration (stage II) and aeration/recirculation (stage III). The system was able to treat landfill leachate with soluble chemical oxygen demand and ammonia removal between 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 22 publications
2
10
0
3
Order By: Relevance
“…18 as TWW replaced BG11 medium. It is consistent with the findings mentioned in another section regarding nitrogen rich medium [27][28][29] . Intracellular sugar presented high content in TWW with KWE compared to TWW without modification.…”
Section: Chlorophylls and Carbohydratessupporting
confidence: 93%
See 1 more Smart Citation
“…18 as TWW replaced BG11 medium. It is consistent with the findings mentioned in another section regarding nitrogen rich medium [27][28][29] . Intracellular sugar presented high content in TWW with KWE compared to TWW without modification.…”
Section: Chlorophylls and Carbohydratessupporting
confidence: 93%
“…It was observed in ref. 28 that when nitrogen is sufficient the protein content and carbohydrates is increasing and lower lipids content are gained. The same direction confirmed in ref.…”
Section: Chlorophylls and Carbohydratesmentioning
confidence: 99%
“…For nitrogen (Table 2), the pilot system removed TKN (82%) and NH 4 þ -N (84%) efficiently during period 1, with residual concentrations of TKN and NH 4 þ -N amounting to 242 and 166 mg/L, respectively. According to previous results (Martins et al, 2013), the main processes of nitrogen transformation during this period were biomass settling (64-79%), ammonia volatilization (17-27%) and algae assimilation (1-6%). Applying the artificial aeration (period 2), it was possible to obtain TKN and NH 4 þ -N removal efficiencies of 95 and 96%, respectively.…”
Section: Resultssupporting
confidence: 64%
“…Martins et al (2013) [40] studied a pilot-scale landfill leachate treatment system utilizing a wild consortium of bacteria and microalgae where a series of three ponds and a rock filter was operated for 111 weeks with a continuous flow rate of leachate as 200 L per day. The study reported three different operation phases (I: conventional operation, II: aeration and III: aeration/recirculation) where COD removal and ammonia removal varied between 35-82% and 75-99%, respectively.…”
Section: Pilot-scale Studiesmentioning
confidence: 99%